Papers of Kenneth Starr - Starr, Kenneth W. (1934)
Correspondence and notes, notebooks, photographs (1 folio item), certificates, (folios), exam results, printed material from medical journals, articles about Shakepeare's use of medicine from the journal Medical Life, a bound, published copy of an essay written by Starr which won the Jacksonian Prize awarded by the Council of the Royal College of Surgeons of England in 1944 entitled The causation and treatment of delayed union in fractures of the long bone, and a bound, inscribed, reprint from the Bulletin of the Post-Graduate Committee in Medicine, University of Sydney, Vol. 22, no. 11, Feb. 1967 containing the annual post-graduate oration given by Sir Kingsley Norris and entitled "Major-General Sir Neville Howse, Vic."
Manuscript reference no. : MS 5688.
Guide to collections of manuscripts relating to Australia
Kenneth Starr (1908-1976), Kt. 1971, C.M.G. 1956, O.B.E., E.D., M.B. Syd., M.S. Melb., F.R.C.S., F.A.C.S., F.R.A.C.S. was born in Wellington N.S.W. He was educated at Forth Street High School and Sydney University where he won many scholastic prizes. He became a prominent surgeon in Sydney and served on many medical advisory boards and committees. He was duly honoured for his services to medicine. He married Alison Howse, daughter of the late Sir Neville Howse who was a well known doctor.
Keywords: Starr, Kenneth W. -- Archives; Surgeons -- Australia -- Archives; Surgeons